The Effect of Edible Mushroom on Health and Their Biochemistry - Anmut Assemie; Galana Abaya (International Journal of Microbiology)
Edible mushrooms are fungi that can be seen with the naked eye and are relatively easy to gather by hand. This review article highlights the health benefit and the biochemistry of several mushroom species. Agaricus bisporus, Pleurotus species. Lentinus edodes, and Volvariella species are the most acceptable varieties among the cultivated mushroom. Various biochemical methods such as methanol, ethanol, and water extract of different parts of the edible mushroom in the laboratory have been applied to determine and/or quantify the presence and effectiveness of their chemical compounds, food value, and medicinal properties. They contain varying amounts of carbohydrates, proteins, nucleic acids, lipids, minerals, terpenoids, phenolic compounds, steroids, and lectins and vitamins, as well as lowering cholesterol levels in the body. Due to the presence of those vital nutrients, mushrooms are the best food item with high nutritional value. These compounds have a wide range of therapeutic effects and can act as immunomodulatory, anticarcinogenic, antiviral, antioxidant, and anti-inflammatory agents. Routine consumption of edible mushrooms would give adequate protection due to the presence of all the necessary nutrients from them. Therefore, edible mushrooms are herbal antibiotics to many diseases as well as various cancers of humans.